Policy implementation and financial incentives for nurses in South Africa: a case study on the occupation specific dispensation - THOMAS, STEPHEN (My University, 2013)
Background: In 2007, the South African government introduced the occupation-specific dispensation (OSD), a financial incentive strategy, to attract, motivate, and retain health professionals in the public sector. Implementation commenced with the nursing sector, but there have been unintended negative consequences. Objective: First, to examine implementation of the OSD for nurses using Hogwood and Gunn's framework that outlines 'perfect implementation' pre-conditions. Second, to highlight the conditions for the successful implementation of financial incentives. Methods: A qualitative case study design using a combination of a document review and in-depth interviews with 42 key informants. Results: The study found that there were several implementation weaknesses. Only a few of the pre-conditions were met for OSD policy implementation. The information systems required for successful policy implementation, such as the public sector human resource data base and the South African Nursing Council register of specialised nurses were incomplete and inaccurate, thus undermining the process. Insufficient attention was paid to time and resources, dependency relationships, task specification, and communication and coordination. Conclusion: The implementation of financial incentives requires careful planning and management in order to avoid loss of morale and staff grievances.
PUBLISHED
Keywords: Health workers; International Development; International Integration